This I Believe - Burchard, John E. (John Ely) (Tufts Archival Research Center, 2006)
John Burchard admits his fear, and describes his belief that life cannot be lived in fear, and that the solution in the face of the current threats to "Western Civilization" is to embrace the diversity that America was founded upon, and to strive for union between world nations, despite such a union's newness and unfamiliarity.